Understanding Indonesia's Cyber Security Policies: Opportunities and Challenges In The Digitalization Transformation Era - Dimas Febriawan; Hizra Marisa (JOELS: Journal of Election and Leadership, 2024)
This paper will discuss the understanding of Indonesia's policies in Cyber Security, in terms of technical aspects and social effects. Where the era of digital transformation raises new risks and threats, namely Cyber Security. It is important for the government, as executor and supervisor, to identify potential risks and threats to ensure cyber security and efforts to build community digital literacy during the digital transformation era. The efficiency of the measures developed and implemented to minimize risks and eliminate threats to national cybersecurity depend on the quality and appropriateness of the implemented policies. From the research results found that a comprehensive approach to analyzing the risks and threats posed by cyber threats in the era of digital transformation is needed and must cover all related processes, both technical and non-technical, in particular the relations between the actors involved. This creates significant opportunities and challenges for Indonesia's future, especially in matters of national defense security from hacking threats and other cyber problems